Discretion of Government Officials in the Perspective of Corruption Crime Reviewed from the Theory of Criminal Removal Reason - Altje Agustin Musa; Jemmy Sondakh; Wempie Jh. Kumendong; Caecilia J.J. Waha (Journal of The Community Development in Asia, 2022)
Providing welfare for all citizens is the goal of the Indonesian state. In government administration, government officials are often faced with concrete social situations urgently to be addressed, while regulations are unclear. To overcome government stagnation, government officials are given the authority to act based on their own considerations, called discretion. The study aims to analyze the discretionary case and find the relationship between discretion in the perspective of corruption and the theory of criminal removal reason. The study finds that Criminal Code regulates Criminal Removal Reasons concerning defending to save on body, soul, or goods of someone/others, not government officials discretion to defend social interest. The Corruption Law does not regulate Criminal Removal Reason. In judicial corruption in Indonesia, Government officials' discretion was not sentenced because the decision/act is based on considerations of urgency, for the public interest, and does not benefit the government officials/others.